2018
DOI: 10.1111/jfbc.12580
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro antioxidant properties ofMuscari comosumbulbs and their inhibitory activity on enzymes involved in inflammation, post-prandial hyperglycemia, and cognitive/neuromuscular functions

Abstract: Extracts of Muscari comosum bulbs, a traditional Mediterranean food, were analyzed by high performance liquid chromatography for polyphenol content and tested for their activity on free‐radicals and enzymes that might be involved in human health. The extracts revealed the presence of phenolic acids and flavonoids with antioxidant and anti‐inflammatory properties. Antioxidant activity was determined by evaluating the radical scavenging activity toward 2,2‐diphenyl‐1‐picrylhydraziyl (DPPH˙), nitric oxide (˙NO), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 38 publications
(68 reference statements)
2
18
0
Order By: Relevance
“…Total phenolic and flavonoid contents found in this study are more similar with those reported by Loizzo et al (2010) [ 13 ] and with those reported in our previous work for the aqueous methanolic bulb extract [ 16 ]. As reported by several authors [ 19 , 20 ], the amount of phenolic compounds represents an important indicator of antioxidant capacity.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Total phenolic and flavonoid contents found in this study are more similar with those reported by Loizzo et al (2010) [ 13 ] and with those reported in our previous work for the aqueous methanolic bulb extract [ 16 ]. As reported by several authors [ 19 , 20 ], the amount of phenolic compounds represents an important indicator of antioxidant capacity.…”
Section: Discussionsupporting
confidence: 93%
“…MET70 had the highest amounts of total polyphenols and flavonoids and demonstrated the best radical scavenging activity vs. DPPH and O 2 − . In a previous study [ 16 ], twelve different compounds were identified in the HPLC profile of 70% methanol extract of M. comosum bulbs, seven of them were phenolic acids (gallic, vanillic, chlorogenic, caffeic, syringic, p -coumaric acid and ferulic) and five were flavonoids (catechin, epicatechin, rutin, naringenin and kaempferol).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison with other work carried out on L. comosa bulbs, the study carried out by Larocca et al in Italy reported a yield of 7.61 ± 0.10% for the extract prepared by the hydroalcoholic solvent (water/methanol 70%) by maceration using centrifugation of 80 rpm (rotation per minute) for 24 hours at 30°C [33]. Another study conducted by Loizzo et al [34] in Italy on L. comosa bulbs showed that the yield was 3.16% for the ethanolic extract prepared by maceration for 48 hours compared to 1.3% for the macerated ethanolic extract of Moroccan L. comosa bulbs.…”
Section: Yields Of Aqueous and Organic Extractions Of Leopoldia Comosa (L) Bulbsmentioning
confidence: 63%